A new species of Reticulana from the Bismarck Archipelago (Lepidoptera: Erebidae) - Zilli, Alberto (Fragmenta entomologica, 2022)
Reticulana sculpta sp. n., a second species of the hitherto monobasic genus Reticulana, is described from New Ireland (Bismarck Archipelago). The new species is similar to the congener R. costilinea from New Guinea, from which it can easily be distinguished by features of the wing pattern and the genitalia